2019
DOI: 10.1021/acs.jnatprod.9b00609
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Strategy for Identification of Highly Unstable Bacillaenes

Abstract: Exploration of unstable compounds is a rarely explored area of natural product research. We describe the integration of genomic and metabolomic analyses with bioassay-guided compound mining to effectively explore unstable bacillaenes. New bacillaene structures (2, 4, and 5) were identified from compound mixtures using the DANS-SVI (differential analysis of 2D NMR spectrum−single spectrum with variable intensities) method, which were further verified by the isolation of the pure compounds under strictly control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…Decomposition of the non-gBAEs was more easily triggered compared to the glycosylated analogues. This result revealed that the glycosylation stabilizes the bacillaene scaffold, which supports our previous suggestion …”
Section: Results and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Decomposition of the non-gBAEs was more easily triggered compared to the glycosylated analogues. This result revealed that the glycosylation stabilizes the bacillaene scaffold, which supports our previous suggestion …”
Section: Results and Discussionsupporting
confidence: 92%
“…The molecular formulas of 1–3 were established as C 34 H 48 N 2 O 6 , C 40 H 58 N 2 O 11 , and C 40 H 60 N 2 O 11 , respectively, on the basis of the HR-ESIMS data ([M + H] + at m / z 581.3595, 743.4163, and 745.4280). Compounds 1 and 3 were confirmed to be bacillaene A and 14′,15′-dihydro-bacillaene B, respectively, as reported in our earlier work, and 2 was identified as bacillaene B by 1D and 2D NMR data assignments (Figure S7 and Table S1). Compounds 1 and 2 , being quantified by the standard curves, underwent time- (0–48 h) and dose-dependent (0.1–10 μg/mL) stability tests at normal bioassay conditions (aqueous solution system, 37 °C, in the dark) using UPLC-MS. As shown in Figure S8, bacillaene A ( 1 ) was rather unstable in aqueous solution.…”
Section: Results and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Despite antibacterial activity of this antibiotic against multi-drug-resistant bacterial isolates, for many years, characterization of bacillaene using the traditional methods based on fractionations was proved challenging, owing to its chemical instability [11]. On exposure to light or room temperature, bacillaene decomposes rapidly, which hindered earlier attempts to identify the biosynthetic pathway of this antibiotic molecule [79]. Antibacterial polyketide bacillaene synthesized by B. velezensis FZB42, exhibited a minor extent of bacteriostatic effect against Erwinia amylovora, a causal agent of fire blight disease [32].…”
Section: Bacillaenementioning
confidence: 99%